Cross-linked porous polyarylene ether nitrile films with ultralow dielectric constant and superior mechanical properties. (27th October 2022) - Cao, Tong; Wang, Lingling; Lin, Guo; An, Yanjie; Liu, Xiaobo; Huang, Yumin
Abstract: Porous polymer materials with low dielectric constant, dielectric loss and excellent mechanical properties are expected to be widely used in the field of microelectronic devices. In this work, polyarylene ether nitrile containing trifluoromethyl and carboxyl groups (PEN) are designed and synthesized and then the cross-linked porous PEN films were successfully prepared by using 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIBF4 ) as porogen and bisphenol-AF epoxy (BAFE) as crosslinker. Due to the introduction of low polarizability trifluoromethyl group and porous structures, porous PEN films show ultralow dielectric constants and hydrophobic surfaces with water contact angles greater than 100°. Moreover, benefiting from the construction of the cross-linked networks, porous low-dielectric PEN films are demonstrated to simultaneously possess excellent mechanical properties. They show excellent flexibility, which can be curled without breaking. Specially, PEN-E-20 film shows high thermal stability (T5%  = 486 °C), ultralow dielectric constant (1.47 at 1 MHz) and dielectric loss (0.004 at 1 MHz), superior mechanical properties (tensile strength of 67 MPa and tensile modulus of 2080 MPa). This strategy will provide a new idea for the design and preparation of flexible, ultralow dielectric materials. Graphical abstract: Image 1 Highlights: The cross-linked porous PEN films with ultralow dielectric constant and superior mechanical properties were prepared. The cross-linked networks were constructed to improve the performance of porous films. The physical pore former EMIBF4 was introduced to precisely control pore size and porosity.